(untitled) (Environment & Health, 2021)
A retrospective and prospective analyses of the rate of incidence and prevalence of diseases of the population of Ukraine over 1990-2017 were carried out on the basis of sectoral statistical reports and professional editions, which made it possible to characterize the current state of health and identify the tendencies in the incidence and disease prevalence in the country. Objective: We studied and analyzed the tendencies of the health state of the population in Ukraine. Materials and methods: We used the data of the sectoral statistical reports and professional editions over 1990-2017, as well as the annual report “On the State of Health of the Population, Sanitary-and-Epidemiological Situation, and Results of the Activity of Health Care System” by the Ministry of Health of Ukraine, State Institution «Ukrainian Institute for Strategic Studies, Ministry of Health of Ukraine». The method of the statistical analysis of the factual and analytical material was used as a main one, it forms a holistic view of health and medico-demographic situation in the country. Results: During the years of Ukraine’s independence, insufficient attention has been paid to the problems of health improvement. The population numbers is falling sharply. In Ukraine, health care costs are low in comparison with the European countries. The structure of morbidity has changed over the last 10-15 years. The most vulnerable groups: children and adolescents, the elderly are of particular concern. An important role in the formation of morbidity rates is played by chronic non-communicable diseases, their level increased significantly in 2005-2010. The general pathological incidence of school-age children in those years also increased and had a significantly higher level among girls than boys. The incidence rate of mental and behavioral disorders in Ukraine has increased. The prevalence of mental and behavioral disorders had its own features in different regions. The rates of incidence and prevalence of diseases in the children of 0-17 years old of age were quite high and had a wavy nature. Conclusions: The implementation of the state and sectoral measures for the improvement of the health of the population of Ukraine, a cardinal reconstruction of the public view regarding the causes and consequences of a significant deterioration in the health of the population can be solved by a radical way of the preservation and strengthening of both personal and public health.